ANALISIS KEMAMPUAN AFEKTIF PEMBELAJAR DARING PADA PROGRAM STUDI PENDIDIKAN EKONOMI UNIVERSITAS MUHAMAMADIYAH BENGKULU - Erwani Yusuf; Helmarini Helmarini; Ayudho Selviani (STKIP Persada Khatulistiwa Sintang, 2021)
This study aims to analyze how children's learning achievement in online learning during the Covid-19 pandemic. The type of research used is qualitative research with a descriptive approach. The data collection techniques in this study used deep interview techniques and documentation which was based on valid data. The result of the study was that the Covid-19 pandemic had a major impact on children's learning achievement. In learning in online learning students experience more difficulties in learning. The learning achievement of children is difficult to monitor directly by the teacher. The application of effective and efficient learning methods in online learning will affect good learning achievement. There are other factors, namely external factors, namely the family which greatly influences children's learning achievement